CORRELATION ANALYSIS BETWEEN STUDENTS' KNOWLEDGE IN MEDAN CITY AND THE PREVALENCE OF KIDNEY FAILURE SYMPTOMS IN INDONESIA DUE TO POOR LIFESTYLES - Friska, Mutia; Susanti, Nofi; Tanjung, Adillah Maharani; Nst, Sabrina Cahyati (HEARTY, 2025)
This journal will convey information regarding the relationship between the knowledge of students in the city of Medan and the high rate of kidney failure in Indonesia as a result of poor lifestyle patterns. The theme surrounding the correlation between students' knowledge in Medan City and the prevalence of kidney failure in Indonesia as a result of poor lifestyles is also presented based on data quoted by researchers from previous journals, data from Riskesdas and the Ministry of Health, and also results from questionnaire that has been created and distributed by researchers to several respondents who are students in Medan City. The data used by researchers is data regarding kidney failure in Indonesia and in the city of Medan, as well as the results of questionnaires from several respondents containing the knowledge of students in the city of Medan regarding the relationship between the prevalence of kidney failure in Indonesia as a result of patterns bad life. In this research, researchers will also discuss the importance of people's mindset and behavioral patterns in efforts to prevent kidney failure rates in Indonesia, where sufferers are no longer elderly people, but have also attacked young people as well.